(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
أجريت هذه الدراسة لتقييم كفاءة أربع سلالات Pseudomonas chlororaphis MA342 وSerratia .plymuthica HRO-C48 وBacillus subtillis B2g وB. subtillis FZB27 على تحفيز المقاومة الجهازية ضد فيروس موزاييك الخيار في نباتات البندورة في الزراعة المحمية. عوملت البذور بالمعلق البكتيري لكل سلالة على حدا بتركيز 9 ×910 وحدة تكوين مستعمرة / مل ثم أعديت الشتول الناتجة عن هذه البذور بعد 10 أيام من التشتيل. سجل موعد تكشف الأعراض الظاهرية وحسبت نسبة الإصابة وشدة الإصابة والمساحة المحصورة تحت منحني تطور الإصابة وقدر تطور درجات الإصابة خلال فترة التجربة, بالاعتماد على الأعراض الظاهرية وقدر نشاط إنزيم البيروكسيداز. قدرت بعضاً من معايير النمو بعد 30 يوماً من العدوى مثل ارتفاع النبات والوزن الطري والجاف للمجموع الخضري والوزن الطري والجاف للمجموع الجذري. أظهرت النتائج ان معاملة البذور بالمعلقات البكتيرية أدت إلى خفض معنوي في نسبة وشدة الاصابة في النباتات المعاملة والمعداة مقارنة بالنباتات المعداة وغير المعاملة حيث تراوحت نسبة الاصابة مابين 40%, 66.6% مقارنة بالشاهد المعدى غير المعامل 93.33 % دون وجود فروق معنوية بين المعاملات البكتيرية. وتراوحت شدة الاصابة مابين 45.53%, 62.2% للمعاملات البكتيرية مقارنة بالشاهد المعدى غير المعامل 88.86%, ازدياد نشاط إنزيم البيروكسيداز في النباتات المعداة المعاملة مقارنة بالنباتات المعداة غير المعاملة. أدت المعاملة بالبكتيريا إلى ازدياد معنوي في نمو النباتات حيث كان ارتفاع النباتات والوزن الطري والجاف للمجموع الخضري والوزن الطري والجاف للمجموع الجذري للنباتات المعاملة بالبكتيريا والمعداة بالفيروس أعلى منه في النباتات المعداة وغير المعاملة عند LSD5% حيث خفضت البكتيريا من معدل التقزم ومعدل الانخفاض بالوزن الطري والجاف للمجموع الخضري والوزن الطري والجاف للمجموع الجذري الحاصلة بفعل الإصابة بفيروس موزاييك الخيار. The study was conducted to evaluate the efficiency of Pseudomonas chlororaphis MA342, Serratia plymuthica HRO-C48K, Bacillus subtillis B2g, B. subtillis FZB27 to induce systemic resistance in Tomato plants against Cucumber mosaic virus (CMV) under greenhouse conditions. Tomato seeds submerged in suspension of Pseudomonas chlororaphis MA342, Serratia plymuthica HRO-C48, Bacillus subtillis B2g and B. subtillis FZB27 9×109cfu . plants emerged from these seed were inoculated with CMV after 10 days of planting. The time of beginning symptoms was recorded, Disease incidence, disease severity, area under disease progress curve AUDPC, progress of infection disease degrees during the study period were calculated using virtual symptoms . pyroxidas enzyme activity was determined, Some growth parameters such as Plant height, foliage fresh weight, root fresh weight , foliage dry weight, root dry weight were observed after 30 DAI. Results of this study showed that seed treatment with Pseudomonas chlororaphis MA342, Serratia .plymuthica HRO-C48, Bacillus subtillis B2g, B. subtillis FZB27 significantly decreased the diseases incidence on treated and inculated plants which ranged between 40% - 66.66% ,compared with un treated and inculated control 93.33% Without the presence of significant differences between the bacterial treatments. significantly decreased the diseases severity on treated plants which ranged between 45.53 %- 62.2% compared with inculated and un treated control 88.86% .Without the presence of significant differences between the bacterial treatments. Peroxidas activity on treated plants increased by Compared with untreated plants. Seed treatments with bacteria significantly increased the plant growth. The plant height , fresh and dry weight of foliage, fresh and dry weight of root on treated plants were significantly higher than those of inculated and un-treated plants according to LSD 5%.where bacteria reduced the rate of stunting and the rate of decline mild and dry weight of foliage and mild and dry weight of the root occurring due to infection with the Cucumber mosaic virus (CMV).